Environmental impact of biodegradable food packaging when considering food waste. (10th April 2018) - Dilkes-Hoffman, Leela S.; Lane, Joe L.; Grant, Tim; Pratt, Steven; Lant, Paul A.; Laycock, Bronwyn
Abstract: From a waste management perspective, high-barrier, multi-layer, biodegradable food packaging could be a useful replacement for current multi-layered packaging that is non-recyclable and non-degradable. Whilst there is still technical research required, it is envisioned that a biodegradable thermoplastic starch (TPS) and polyhydroxyalkanoate (PHA) layered material could be a promising target. However, there is currently limited research identifying what environmental trade-offs are associated with using such a material – meaning there is no guidance regarding what design characteristics are important to consider during development of such packaging. The aim of this study was to quantify the greenhouse gas (GHG) trade-offs associated with using the proposed biodegradable packaging and identify the important design considerations. To our knowledge this is the first study to discuss the implications of including food wastage when assessing biodegradable food packaging materials. It also considers the impacts of landfill methane capture efficiency, which is an important aspect as biodegradable packaging may release methane when disposed of in a landfill whereas non-biodegradable packaging is inert. However, a key result is that when food waste is included in the system boundaries, it contributes over 50% of the GHG emissions associated with the system, regardless of whether the package is biodegradable or not. This shows that even for biodegradable packaging, reducing food waste is a key design consideration. In fact, the negative environmental impacts associated with disposal of a PHA-TPS packaging in landfill with low gas capture rates can actually be offset if the package reduces food wastage (beef) by approximately 6%. The overarching result is that a PHA-TPS food packaging only delivers positive GHG outcomes if it reduces food wastage or increases the viability of biological food waste processing. Highlights: Food waste dominates a food packaging LCA regardless of the packaging material. Reducing food waste can negate the emissions of a biodegradable package in landfill. Biodegradable packaging has an overall negative impact if it increases food wastage.